Wrist torque strength distribution among elementary to middle school children during bottle opening. (1st July 2021) - Alrashdan, Abdalla Issa
This paper provides a wrist torque strength distribution for children. The data was collected for 540 male and female subjects aged 6 to 14 years. Different cap diameters were tested to simulate common bottle cap diameters. Statistical inferences are used to form age groups with distinctive torque strengths. The data are clustered based on age, gender, and bottle diameter. The torque strength for each cluster is tabulated in standard anthropometric tables. The required torque to release the cap from different bottles' necks of leading beverage companies is investigated and compared with the torque strength of each group. It was found that many of the available drink bottles packed for children require torque strength which is not suitable for most of them.